Production Costs and Profitability for Selected Greenhouse Grown Annual Bedding Plants: Partial Enterprise Budgeting and Sensitivity Analysis - Hayk Khachatryan; Xuan Wei (EDIS)
The objective of the research described in this publication was to estimate the cost of greenhouse production for selected annual bedding plants and help growers to determine how the particular crop they are growing influences profitability.